Picture, print and promote - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Rinderpest is a deadly disease which wiped out 80-90% of all cattle and wild ruminants across Africa a hundred years ago, and has been a recurrent problem ever since. The Pan African Rinderpest Campaign (PARC) was set up in 1986 with the aim of...